Logic Design - Chapter 3: Boolean Algebra
Upcoming SlideShare
Loading in...5
×

Like this? Share it with your network

Share

Logic Design - Chapter 3: Boolean Algebra

  • 471 views
Uploaded on

- Describing Logic Circuits Algebraically. ...

- Describing Logic Circuits Algebraically.
- rules of evaluating a Boolean expression.
- Boolean Theorems.
- DeMorgan's Theorem.
- Universality of NAND and NOR Gates.
- Alternate Logic Gate Representations.
- Minterms and Maxterms.
- STANDARD FORMS.

More in: Education , Technology
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Be the first to comment
No Downloads

Views

Total Views
471
On Slideshare
471
From Embeds
0
Number of Embeds
0

Actions

Shares
Downloads
34
Comments
0
Likes
1

Embeds 0

No embeds

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
    No notes for slide
  • We can say that X = A’BC (A’D’).
  • X = [D+ ((A+B)C)']•E = [D+((A+B)’+C’)]•E = [D+(A’B’+C’)]•E = [1+(1•1+0)]•1 = [1+(1+0)]•1 = [1+1] •1 = 1•1 = 1. 
  • X in the first diagram can = A’BC (A’D’)
  • Commutative = Eltabdel - Associative = El2edmag - Distributive = Eltawze3 - Absorption = El2emtsas (mass)
    Proof:- x+xy = x.1+x.y = x(1+y) = x.1 = x 
  • AND will be OR and nwza3 el bar 3lehom el 2, w el3ks sa7e7 
  • Universal because it do the 3 operation INVERTER, AND & OR
  • Universal because it do the 3 operation INVERTER, OR & AND.

Transcript

  • 1. CHAPTER 3 Boolean Algebra
  • 2. Contents         Describing Logic Circuits Algebraically rules of evaluating a Boolean expression Boolean Theorems DeMorgan's Theorem Universality of NAND and NOR Gates Alternate Logic Gate Representations Minterms and Maxterms STANDARD FORMS 2
  • 3. Describing Logic Circuits Algebraically  OR gate, AND gate, and NOT circuit are the basic building blocks of digital systems 3
  • 4. Circuits containing Inverters 4
  • 5. Evaluating Logic Circuit Outputs  Let A=0, B=0, C=1, D=1, E=1 X = [D+ ((A+B)C)'] • E = [1 + ((0+0)1 )'] • 1 = [1 + (0•1)'] • 1 = [1+ 0'] •1 = [1+ 1 ] • 1 =1 5
  • 6. Rules of evaluating a Boolean expression First, perform all inversions of single terms; that is, 0 = 1 or 1 = 0.  Then perform all operations within parentheses.  Perform an AND operation before an OR operation unless parentheses indicate otherwise.  If an expression has a bar over it, perform the operations of the expression first and then invert the result.  6
  • 7. Determining Output Level from a Diagram 7
  • 8. Boolean Theorems 8
  • 9. Multivariable Theorems (9) (10) (11) (12) (13.a) (13.b) (13.c) (14) (15) (16) x + y = y + x (Commutative law) x • y = y • x (Commutative law) x+ (y+z) = (x+y) +z = x+y+z (Associative law) x (yz) = (xy) z = xyz (Associative law) x (y+z) = xy + xz (Distributive law) x + yz = (x + y) (x + z) (Distributive law) (w+x)(y+z) = wy + xy + wz + xz x + xy = x (Absorption) [proof] x + x'y = x + y (x +y)(x + z) = x +yz 9
  • 10. Proof of (14, 15, 16) x + xy x + x’y = x (1+y) = x • 1 [using theorem (6)] = x [using theorem (2)] = ( x + x’) (x + y) [theorem 13b] = 1 (x +y) = (x + y) (x +y)(x + z) =xx + xz + yx + yz = x + xz + yx + yz = x (1+z+y) +yz = x . 1 + yz = x + yz 10
  • 11. DeMorgan's Theorem (18) (x+y)' = x' • y'  (19) (x•y)' = x' + y'  Example  X = [(A'+C) • (B+D')]' = (A'+C)' + (B+D')' = (AC') + (B'D) = AC' + B'D 11
  • 12. Three Variables DeMorgan's Theorem (20) (x+y+z)' = x' • y' • z'  (21) (xyz)' = x' + y' + z‘   EXAMPLE:  Apply DeMorgan’s theorems to each of the following expressions:  (a) ( A + B + C) D  (b) ABC + DEF  (c) A B + CD + EF 12
  • 13. Universality of NAND Gates 13
  • 14. Universality of NOR Gates 14
  • 15. Alternate Logic Gate Representations 15
  • 16. Minterms and Maxterms x y z 0 0 0 Minterms Term Designation x' y’ z' m0 Maxterms Term Designation x+y+z M0 0 0 1 x' y' z M1 0 1 0 x' y z’ m2 0 1 1 x' y z m3 1 0 0 x y' z’ m4 1 0 1 x y' z m5 1 1 0 x y z’ m6 1 1 1 xyz m7 x+y+z’ +y x+y’+z +y -t- Z x+y’+z’ + y' +2 x'+y+z +y' + '+y+z’ xt , '+y + '+y’+z x z 4-'+y’+z’ x 2' M1 M2 M3 M4 M5 M6 M7 2 16
  • 17. Canonical FORMS  There are two types of canonical forms:   the sum of minterms The product of maxterms 17
  • 18. Sum of minterms  f1 = x'y'z + xy'z' + xyz = m1 + m4 +m7  f2 = x'yz + xy'z + xyz’ + xyz = m3 + m5+ m6 + m7 x 0 0 0 0 1 1 1 1 y 0 0 1 1 0 0 1 1 Z 0 1 0 1 0 1 0 1 f1 0 1 0 0 1 0 0 1 f2 0 0 0 1 0 1 1 1 18
  • 19. Product of maxterms The complement of f1 is read by forming a minterm for each combination that produces a 0 as:  f1’=x’y’z’ + x’yz’ + x’yz + xy’z + xyz’   f1 = (x + y + z)(x + y' + z)(x + y' + z' )(x’+ y + z)(x’ + y' + z) = Mo M2 M3 M5 M6 Similarly  f2 = ?  19
  • 20. Example: Sum of Minterms  Express the Boolean function F = A + B'C in a sum of minterms.  F=A+B'C = ABC + ABC' + AB'C + AB'C' + AB'C + A'B'C 20
  • 21. Example: Product of Maxterms  Express the Boolean function F =xy' + yz in a product of maxterm form.  F = xy' + yz = (xy' + y)(xy' + z) = (x + y)(y' + y)(x + z)(y' + z) = (x + y)(x + z)(y' + z) = (x + y + zz')(x + yy' + z)(xx' + y' + z) = (x + y + z)(x + y + z')(x+y + z)(x+y’+ z)(x + y' + z)(x'+y'+z) = (x + y + z)(x + y + z') (x + y' + z) (x'+y'+z) = M0 M1 M2 M6 = Π (0,1,2,6) 21
  • 22. STANDARD FORMS  There are two types of standard forms:   the sum of products (SOP) The product of sums (POS). 22
  • 23. Sum of Products The sum of products is a Boolean expression containing AND terms, called product terms, of one or more literals each. The sum denotes the ORing of these terms.  F = xy + z +xy'z'. (SOP)  23
  • 24. Product of Sums A product of sums is a Boolean expression containing OR terms, called sum terms. Each term may have any number of literals. The product denotes the ANDing of these terms.  F = z(x+y)(x+y+z) (POS)  F = x (xy' + zy) (nonstandard form)  24